Risk Factors for Mortality in Children with Hospital-Acquired Pneumonia in Dr. Soetomo General Hospital Surabaya - Diska Hanifah Nurhayati; Retno Asih Setyoningrum; Arie Utariani; Ira Dharmawati (Jurnal Respirasi, 2021)
Introduction: Hospital-Acquired Pneumonia (HAP) is a nosocomial pneumonia that brings negative impacts, such as prolonged hospital stay and increased cost. Previous studies often discussed about the risk factors of HAP mortality in adult patients rather than in children. This study aimed to analyze the risk factors of mortality in children with HAP.Methods: This was a retrospective observational analytic study using cross sectional method with total sampling. A total of 73 children were enrolled in this study, consisted of inpatients at Pediatric Inpatient Room Dr. Soetomo General Hospital Surabaya who met the inclusion and exclusion criteria. Independent variables were gender, age, onset of HAP, length of stay (LOS), comorbidities, birth weight, type of breastfeeding, the use of mechanical ventilation (MV), and response to therapy. Dependent variable was mortality. The data were collected from medical records, which later were analyzed by bivariate and multivariate analysis.Results: The mortality of children with HAP was 23.3%. Bivariate analysis showed that age (p = 0.009), the use of MV (p = 0.029), and response to therapy (p = 0.036) were proven to affect mortality in children with HAP in Dr. Soetomo General Hospital Surabaya. In addition, the use of MV was the significant risk factor (p = 0.023) given by the multivariate analysis. Gender, onset of HAP, LOS, comorbidities, and type of breastfeeding were not proven to be the risk factors for mortality.Conclusion:Mortality in children with HAP in Dr. Soetomo General Hospital Surabaya was significantly affected by children’s age, the use of MV, and response to therapy. This information might be used as early signs and treatment strategies for children with HAP which lead to the decrease of hospital mortality.